2005
DOI: 10.1159/000093128
|View full text |Cite
|
Sign up to set email alerts
|

GABA<sub>B1</sub> Knockout Mice Reveal Alterations in Prolactin Levels, Gonadotropic Axis, and Reproductive Function

Abstract: γ-Aminobutyric acid (GABA) has been implicated in the control of hypophyseal functions. We evaluated whether the constitutive loss of functional GABAB receptors in GABAB1 knockout (GABAB1–/–) mice alters hormonal levels, under basal and stimulated conditions, and reproductive function. The serum hormone levels were measured by radioimmunoassay, the estrous cyclicity was evaluated by vaginal lavages, and the mating behavior was determined by the presence of vaginal pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 122 publications
5
53
0
Order By: Relevance
“…In addition to the results shown here, we have described previously that adult body weights showed no significant genotype differences for either sex (15), similar to PND4 mice. Moreover, fasted blood glucose did not differ between genotypes in adults, but fasted insulin levels were increased in adult GABA B1 KO males (7), suggesting insulin resistance in this sex.…”
Section: Body Weight Pancreatic Weight and Glucose Homeostasis In Msupporting
confidence: 89%
See 2 more Smart Citations
“…In addition to the results shown here, we have described previously that adult body weights showed no significant genotype differences for either sex (15), similar to PND4 mice. Moreover, fasted blood glucose did not differ between genotypes in adults, but fasted insulin levels were increased in adult GABA B1 KO males (7), suggesting insulin resistance in this sex.…”
Section: Body Weight Pancreatic Weight and Glucose Homeostasis In Msupporting
confidence: 89%
“…Mice were genotyped by PCR analysis, as described previously (15). All animals were housed in groups and maintained at 22°C on a 12:12-h light-dark cycle with free access to laboratory chow and tap water.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum insulin was assessed by RIA using an anti-rat insulin antibody (Sigma, St. Louis, Missouri, USA) and standard rat insulin provided by Laboratorios Beta (Buenos Aires, Argentina). TSH was determined by competitive RIA according to the procedure outlined by Catalano et al (2005). The levels of total T4, estradiol and testosterone were measured using competitive RIA kits (Immunotech, Marseille, France).…”
Section: Circulating Hormone Measurementsmentioning
confidence: 99%
“…In this regard, we showed that GABA B R subunits have particular ontogenic expression patterns in the rat hypothalamus and the pituitary (9,10) and that their expressions show sexual dimorphisms at early stages of development (8,9). In GABA B1 knockout (GABA B1 KO) mice, which lack functional GABA B Rs (79), we demonstrated that GABA B Rs are involved in regulating basal prolactin (PRL) release in males and that the hypothalamic-hypophyseal-ovarian axis is compromised in females, with significant alterations in cyclicity, postcastration LH increase, and reproduction indexes (14). Because GABA B receptors have been demonstrated to participate in the regulation of the gonadotropic axis, and taking into consideration our previous results in GABA B1 KO mice, we studied different parameters involved in the regulation of the hypothalamic-pituitary gonadotropic axis in adult male and female GABA B1 KO mice to establish the impact of the loss of functional GABA B Rs.…”
mentioning
confidence: 99%